Tumor plasticity and therapeutic resistance in oncogene-addicted non-small cell lung cancer: from preclinical observations to clinical implications. (April 2023) - Toyokawa, Gouji; Bersani, Francesca; Bironzo, Paolo; Picca, Francesca; Tabbò, Fabrizio; Haratake, Naoki; Takenaka, Tomoyoshi; Seto, Takashi; Yoshizumi, Tomoharu; Novello, Silvia; Scagliotti, Giorgio V.; Taulli, Riccardo
Abstract: The identification of actionable targets in oncogene-addicted non-small cell lung cancer (NSCLC) has fueled biomarker-directed strategies, especially in advanced stage disease. Despite the undeniable success of molecular targeted therapies, duration of clinical response is relatively short-lived. While extraordinary efforts have defined the complexity of tumor architecture and clonal evolution at the genetic level, not equal interest has been given to the dynamic mechanisms of phenotypic adaptation engaged by cancer during treatment. At the clinical level, molecular targeted therapy of EGFR -mutant and ALK -rearranged tumors often results in epithelial-to-mesenchymal transition (EMT) and histological transformation of the original adenocarcinoma without the acquisition of additional genetic lesions, thus limiting subsequent therapeutic options and patient outcome. Here we provide an overview of the current understanding of the genetic and non-genetic molecular circuits governing this phenomenon, presenting current strategies and potentially innovative therapeutic approaches to interfere with lung cancer cell plasticity. Graphical Abstract: ga1 Highlights: Cancer cell plasticity poses a formidable challenge to tumor eradication in oncogene-addicted NSCLC. EMT, NE and SCC transformation are common non-genetic mechanisms of drug resistance observed in patients. Preclinical and translational studies are necessary to identify vulnerabilities linked to phenotypic plasticity. Innovative strategies targeting phenotypic adaptation are required to improve patient outcome.